Utilización de tres niveles de pimienta negra (Piper nigrum) como suplemento energético en gallinas de postura. - Quinchiguango Zumba, Mery Thalia (2022)
This research was developed at Héroes de Paquisha neighborhood, Guamaní parish, Quito Canton, Pichincha Province, different levels of black pepper (0.5%, 1.0% and 1.5%) were used as an energy supplement for feeding laying hens, the project had a duration of 6 weeks, with 48 hens of Lohmann Brown breed of 20 weeks old, a completely randomized design with 4 treatments and 3 repetitions were used. Treatments were; T0 (Base diet - control treatment without addition of black pepper), T1 (Base diet + 0.5% addition of black pepper), T2 (Base diet + 1% addition of black pepper), T3 (Base diet + 1.5% of addition of black pepper). Productive interest variables at the study were weight gain and hens food consumption, production amount and eggs size. With black pepper use as an energy supplement on feeding, a slight increase in weight and/or size of the egg was obtained, but not an increase at egg laying amount. In addition, it was evidenced that higher percentage of black pepper added to the food greater rejection, that is, the palatability of food significantly decreased. The control treatment was the one that reached the highest economic yields because in this the cost of black pepper was not added and there was a greater food consumption. At eggs distribution and sale, it can be seen that there is a preference by a part of consumer for larger eggs. The use of black pepper did not have favorable results when is used as an energy supplement in laying birds, due to low palatability of this ingredient, which is reflected in all productive parameters.